The prognostic significance of improvement in exercise capacity in heart failure patients who participate in cardiac rehabilitation programme. (29th August 2020) - Sabbag, Avi; Mazin, Israel; Rott, David; Hay, Ilan; Gang, Nelly; Tzur, Boaz; Goldkorn, Ronen; Goldenberg, Ilan; Klempfner, Robert; Israel, Ariel
Abstract: Introduction: There are limited contemporary data regarding the association between improvement in cardiovascular fitness in heart failure patients who participate in a cardiac rehabilitation programme and the risk of subsequent hospitalisations. Methods: The study population comprised 421 patients with heart failure who participated in our cardiac rehabilitation programme between the years 2009 and 2016. All were evaluated by a standard exercise stress test before initiation, and underwent a second exercise stress test on completion of 3 ± 1 months of training. Participants were dichotomised by fitness level at baseline, according to the percentage of predicted age and sex norms achieved. Each group was further divided according to its degree of functional improvement, between the baseline and the follow-up exercise stress test. Major improvement was defined as improvement above the median value in each group. The combined primary endpoint was cardiac hospitalisation or all-cause mortality. Results: A total of 211 (50%) patients had low baseline fitness (<73% (median)) for age and sex-predicted metabolic equivalents of task value. Compared to patients with higher fitness, those with a low baseline fitness were more commonly smokers, had diabetes and were obese ( P  < 0.05 for all). Multivariable Cox proportional hazard regression analysis showed that, independent of baseline capacity, an improvement of 5% of predicted fitness was associated with a corresponding 10% reduced risk of cardiac hospitalisation or all-cause mortality ( P  < 0.001). Conclusion: In heart failure patients participating in a cardiac rehabilitation programme, improved cardiovascular fitness is associated with reduced mortality or cardiac hospitalisation risk during long-term follow-up, independent of baseline fitness.